Spectrophotometric investigation of the chemical compatibility of the anticancer drugs irinotecan-HCI and epirubicin-HCI in the same infusion solution - (:unkn) unknown (SPRINGER, 2005)
The use of infusional chemotherapy, especially in an ambulatory setting, absolutely requires that the individual agents remain stable in solution at room temperature and that the drugs be compatible. Because of this, investigation of the chemical compatibilities of chemotherapeutic drug combinations given in the same infusion solution is quite important especially if the drugs are to remain in solution for long periods. Thus, the visual and chemical compatibility of irinotecan and epirubicin in the same infusion solution were investigated using both reference standards and pharmaceutical dosage forms. No sign of incompatibility was observed upon visual examination by means of effervescence, pH change, precipitation and colour change. But a chemical incompatibility was observed using a spectrophotometric method in the spectra of irinotecan-HCl and epirubicin-HCl. The molar ratio of epirubicin-HCl/irinotecan-HCl at which the interaction reached a maximum was found to be 2:1. The chemical interaction occurred immediately after admixing and no visual or spectral change was noticed for 24 h after the interaction had occurred. It is concluded that these drugs are chemically incompatible. While the applicability of these two drugs in combination is investigated in further pharmacological studies, their chemical interaction should also be a consideration. The positive or negative contribution of this interaction to the pharmacological effect of the combination might be of importance, and therefore should be investigated in further clinical trials.
Keywords: irinotecan; epirubicin; chemical compatibility; interaction; spectrophotometry; visual compatibility; PHASE-I; DOXORUBICIN; CANCER